Label-free second harmonic generation imaging of cerebral vascular wall in local ischemia mouse model in vivo. (15th October 2022) - Sun, Hengfei; Wang, Shu; Chen, Jianxin; Yu, Hongbo
Highlights: Morphology of cerebral blood vessels is provided by label-free in vivo SHG imaging. Type III collagen in vascular wall is dominant signal source to SHG imaging. Early and subtle dynamics in vascular wall can be identified by in vivo SHG imaging after local ischemia. Abstract: Second harmonic generation (SHG) imaging is label-free and non-invasive, and it has been extensively applied in multiple biological and medical studies, but not in the brain in vivo . In this study, we modified classical two photon excited fluorescence (TPEF) system to perform in vivo simultaneous TPEF and SHG imaging in the local ischemia mouse model. In cerebral vascular walls, we found strong SHG signal, which co-localized with collagen. In the continuous 2 days' in vivo imaging, this SHG signal remained stable in the local ischemic blood vessel in the initial 4 h, then its signal abruptly increased and got spatially thickened 5 h after thrombosis, and this tendency continued in the following 48 h. This study provides direct and precise timeline of rapid collagen change in cerebral vascular walls in vivo, and reveals the subtle but significant temporal-spatial dynamics of this structural signal during local ischemia. Thus, this cerebral in vivo SHG imaging provides a powerful tool to identify the early and subtle pathological change of collagen around clinical key therapeutic time window.